Memory and the moving image : French film in the digital era - McNeill, Isabelle, Dr (Edinburgh University Press, 2010)
A vital rethinking of memory and the moving image for the digital age, Isabelle McNeill investigates the role of the moving image in cultural memory, considering the impact of digital technologies on visual culture. Drawing on an interdisciplinary range of theoretical resources and an unusual body of films and moving image works, the author examines the ways in which recent French filmmaking conceptualises both the past and the workings of memory. Ultimately the author argues that memory is an intersubjective process, in which filmic forms continue to play a crucial role even as new media come to dominate our contemporary experience. Memory and the Moving Image: Introduces new ways of thinking about the relation between film and memory, arising from a compelling, interdisciplinary study of theories and films Subtly explores the French context while drawing theoretical conclusions with wider implications and applicability Provides detailed and illuminating close readings of varied moving image works to aid theoretical explorations Moves away from auteurist approaches, examining work by canonical directors including Jean-Luc Godard, Chris Marker and Agnès Varda alongside that of less well-known filmmakers such as Claire Simon and Yamina Benguigui Brings together thinkers such as Bergson, Deleuze, Bazin and Barthes with, for example, Rodowick and Mulvey, in an engaging interweaving of theories. Works considered include Jean-Luc Godard's Histoire(s) du Cinéma (1989-98), Yamina Benguigui's Mémoires d'Immigrés (1997), Chris Marker's CD-ROM Immemory (1998), Claire Simon's Mimi (2003), Michael Haneke's Caché (2005) and Agnès Varda's multi-media exhibition, L'Île et Elle (2006).